SOCIAL COMPETENCE AND PSYCHOLOGICAL VULNERABILITY: THE MEDIATING ROLE OF FLOURISHING - Uysal, Recep (SAGE PUBLICATIONS INC, 2015)
This study examined whether flourishing mediated the social competence and psychological vulnerability. Participants were 259 university students (147 women, 112 men; M age = 21.3 yr., SD = 1.7) who completed the Turkish versions of the Perceived Social Competence Scale, the Flourishing Scale, and the Psychological Vulnerability Scale. Mediation models were tested using the bootstrapping method to examine indirect effects. Consistent with the hypotheses, the results indicated a positive relationship between social competence and flourishing, and a negative relationship between social competence and psychological vulnerability. Results of the bootstrapping method revealed that flourishing significantly mediated the relationship between social competence and psychological vulnerability. The significance and limitations of the results were discussed.
Keywords: MENTAL-HEALTH; ATTACHMENT; HAPPINESS; VALIDITY; LIFE; Psychology